Analisis Pemberian Vitamin A pada Balita di Wilayah Kerja Puskesmas Jatimulya Kecamatan Tambun Selatan Kabupaten Bekasi Jawa Barat - Juninda Putri; Andi Julia Rifiana; Febry Mutiariami Dahlan (Malahayati Nursing Journal, 2023)
ABSTRACT Vitamin A is an important nutrient that is needed by the body for growth and resistance to disease. Vitamin A deficiency can cause blindness in children and increase the risk of morbidity and death. To analyze vitamin A administration on toddlers at the Work Area of the Jatimulya Health Center, South Tambun District, Bekasi Regency, West Java in 2023. This study used a descriptive analytic method with a cross sectional approach. The sample in this study was78 respondents, by total sampling technique. The instruments of this study were questionnaires and medical records. The results of the study were tested statistically using the chi-square test and the odds ratio. Based on the results of statistical tests using chi square showed that there was a significant relationship between mother's knowledge and giving vitamin A to toddlers with a p-value 0.05, and there was no significant relationship between family support, mother's attitude, sources of information and the role of cadres by giving vitamin A to toddlers with a p-value of 0.05. Statistical tests using the odds ratio showed that the risk factor for giving vitamin A was knowledge with a value of OR=14,000. The level of mother's knowledge is related to the administration of vitamin A to toddlers. Meanwhile, family support, mother's attitude, sources of information, the role of cadres were not related to giving vitamin A to toddlers in the working area of the Jatimulya Health Center, the risk factor for giving vitamin A to toddlers was mother's knowledge. For mothers who have toddlers are expected to pay more attention to the provision of vitamin A and remember the schedule set by the government. Keywords : Vitamin A, Administration of Vitamin A, Toddlers.  ABSTRAK Vitamin A merupakan zat gizi penting yang sangat diperlukan tubuh untuk pertumbuhan dan daya tahan tubuh terhadap penyakit. Kekurangan vitamin A dapat menyebabkan kebutaan pada anak serta meningkatkan risiko kesakitan dan kematian. Mengetahui analisis pemberian vitamin A pada balita di Wilayah Kerja Puskesmas Jatimulya Kecamatan Tambun Selatan, Kabupaten Bekasi, Jawa Barat Tahun 2023. Penelitian ini menggunakan metode deskriptif analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini sebanyak 78 responden, dengan menggunakan total sampling. Instrumen dari penelitian ini yaitu kuesioner dan rekam medis. Hasil penelitian diuji dengan statistik menggunakan uji chi-square dan odds ratio. Berdasarkan hasil uji statistik menggunakan chi square menujukan bahwa ada hubungan yang bermakna antara pengetahuan ibu dengan pemberian vitamin A pada balita dengan p-value 0,05, dan tidak ada hubungan yang bermakna antara dukungan keluarga, sikap ibu, sumber informasi dan peran kader dengan pemberian vitamin A pada balita dengan p-value 0,05. Uji statistik menggunakan odds ratio menunjukan bahwa faktor resiko terhadap pemberian vitamin A adalah pengetahuan dengan nilai OR=14,000. Tingkat pengetahuan ibu berhubungan dengan pemberian vitamin A pada balita. Sedangkan dukungan keluarga, sikap ibu, sumber informasi, peran kader tidak berhubungan dengan pemberian vitamin A pada balita di wilayah kerja Puskesmas Jatimulya, faktor resiko terjadinya pemberian vitamin A pada balita yaitu pengetahuan ibu. Bagi ibu yang memiliki balita diharapkan lebih memperhatikan pemberian vitamin A dan mengingat jadwal yang telah ditentukan pemerintah. Kata Kunci: Vitamin A, Pemberian Vitamin A, Balita.